Ovarian teratoma associated with struma ovarian: Presentation of 12 cases - Lozada S., Benigno (2015)
12 cases of ovarian teratoma associated with struma is presented. The most frequently it observed between the 3rd. and 4ta. decade of life. We found a slight predominance in the right location annex. 75% of partners to ovarian teratomas struma reached a diameter of 9 cm. The most frequent symptoms and signs were adnexal tumor and to a lesser extent, menorrhagia, and abdominal pain. Furthermore thyroid tissue, tissue structure were more frequently observed: skin and skin, adipose tissue, cartilage and neural tissue.